Implementation of Toraja cultural values to increase students' motivation in learning English at SMKS. SPP. St. Paulus Makale - Tandikombong, Matius; Sirande, Normalia; Lendratri, Ratu (Universitas Cokroaminoto Palopo, 2025)
This research is a quantitative research. The objective this research is to “find out the effectiveness of the implementation of Toraja cultural values ​​to increase students' motivation in learning English”. This research was conducted at SMKS SPP. St. Paulus Makale, ant the population of this research was the eleventh grade students consisting of 20 students and the sample of this Research was chosen by using total sampling technique. It means that all the eleventh grades students were the sampel of this research namely 20 students. The instrument used in this research to collect the data was a questionnaire. The results of this Research show that the application of cultural values ​​in English learning can increase student motivation. This is shown after tabulating pre-test and post-test data, It was found that the t-table = 1,729. and t –test = 4, 613. It means that the t-test is higher than t-table (t-test> t-table) this result showed there was a significant increase in student motivation in learning English after implemented Toraja culture values in learning English .